IDENTIFICATION TARGETED ON toxR GENE AND DETECTION OF VIRULENT FACTOR ENCODING GENES ON Vibrio parahaemolyticus ISOLATED FROM RAW CHICKEN MEAT - Fitrianda, Eka (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2011)
A number of V. parahaemolyticus isolates has been isolated from raw chicken meat samples collected in Pasar raya Padang. Isolation was done using ChromagarTM Vibrio media. Identification of toxR gene was then done to these isolates. toxR is a very specific gene in V. parahaemolyticus species. Detection for the presence of genes encoding virulence factors, in this case were the gene encoding thermostable direct hemolysin (tdh) and TDH related hemolysin (trh) was performed on toxR positive V. parahaemolyticus isolates. Identification of toxR gene and detection of tdh and trh genes were done trough amplification using polymerase chain reaction PCR (method). The results showed that all of the tested V. parahaemolyticus isolates (22 isolates) had toxR gene, but none of isolates has gene encoding the production of virulence factors both tdh and trh.